Implementasi Pembelajaran PAI dengan Strategi Hybrid Learning (HL): Menciptakan Siswa yang Kritis dan Berwawasan Global di Era Society 5.0. - Supardi Ritonga; Mardiana Mardiana; Nabila Nabila; Indah Sahara; Safira Aulia Putri (Journal on Education, 2025)
This study aims to analyze the implementation of the Scientific Learning strategy in Islamic Religious Education (PAI) learning in order to create students who are critical and globally minded in the Society 5.0 era. This approach was chosen because of its relevance in improving critical thinking skills, digital literacy, and the integration of religious knowledge with the rapid development of science and technology. This study uses a library research method with a descriptive qualitative approach, examining various literature from scientific journals, reference books, and related education policy documents. The results of the study show that the Scientific Approach strategy in PAI learning can help students understand the concept of religion in depth, develop analytical skills, and strengthen Islamic values in a global context. In addition, this strategy has also proven to be effective in improving students' digital literacy, allowing them to be actively involved in technologybased learning that is in line with the demands of Society 5.0. Thus, the implementation of the Scientific Approach in PAI is not only relevant to answer the challenges of education in the digital era, but also contributes to shaping a generation of Muslims who are able to compete globally without leaving their religious identity